Chemical modified coconut husk for potassium removal from aqueous solution : Optimization by response surface methodology (RSM) - Nurul Shakira Johari (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
The ecosystem rating today shows the higher rated regarding the pollution on the heavy metal. The most popular adsorbent for the heavy metal is activated carbon. However, the high market demand on the activated carbon make it become more expensive. Thus, many research were conduct to the agricultural waste in order to get the economic bio-sorbent. In this present study, chemical modified coconut husk for potassium removal from aqueous solution: optimization by Response Surface Methodology (RSM) were investigated. The treated coconut husk was treated by concentrated sulfuric acid (H2SO4). The experiment was carried out based on experimental design of the Central Composite Design (CCD) for untreated and treated coconut husk activated carbon on the parameters of adsorbent dosage (0.2-1.0) g, contact time (30-180) min, initial concentration (10-100) mg/L and pH (2-6). Then, the concentration of potassium in the solution were analyzed using Atomic Adsorption Spectrometer (AAS). After that, the results were analyzed using Response Surface Methodology (RSM). The effect of the four parameters on the adsorption of potassium were investigated. The optimum adsorption conditions for both untreated and treated coconut husk activated carbon were found to be 0.80 g, 142.50 min, 92.42 mg/L and pH 3.00, respectively. Under optimal value of process parameters, the maximum removal was found to be 78.78% of untreated and 83.52% of treated coconut husk activated carbon..